Progressão da escoliose neuromuscular e opção cirúrgica na encefalopatia crônica não progressiva infantil: Uma revisão de escopo - Julie Cristine Santos da Silva; Stephanya Covas da Silva; Hildemberg Agostinho Rocha de Santiago; Rafael Menezes Reis (Sociedade Brasileira de Pediatria, 2022)
OBJECTIVE: To carry out a systematic review of the progression of scoliosis in patients with cerebral palsy. METHODS: Systematic review study with searches for journals in the PubMed database from September to December 2020 with specific descriptors associated with the Boolean operator "or" "longitudinal" or "cohort" or "control-case" and "prospective" and " cerebral palsy" and "scoliosis" or "spine deformity" or "spinal deformity" or "neuromuscular". Eligibility criteria for inclusion and exclusion of studies were applied, with subsequent data tabulation. RESULTS: A total of 986 articles were found, only seven articles were eligible for desired data extraction after applying eligibility criteria. CONCLUSION: Age and Gross Motor Function Classification System (GMFCS) can be clinical predictors of scoliosis progression. Scoliosis was more progressive in patients with GMFCS III, IV and V. Patients with a smaller Cobb angle during the bone growth period have a lower chance of curve progression.